Informal methods of testing the reasonings - Wieczorek, Krzysztof A. (Folia Philosophica, 2009)
The aim of the paper is to point that the reasonings may be tested with the methods different from those proposed by formal logic. Scholars involved in the late the XXth-century current of “informal logic” refuse to make the logical entailment of the conclusion from the given premises of the only criteria of the correctness of the reasoning. Instead of this, they propose to take into consideration some other characteristics of reasonings, which traditional logic treats as unimportant or elusive.